The Impact Of Parental Involvement And Self-Efficacy In Anchoring The Psychological Resilience Among Chinese Adolescents With Learning Difficulties: Mediating Role Of Achievement Motivation - Tianyu, Zhao; Masnan, Abdul Halim (South Asian Journal of Social Sciences and Humanities, 2023)
Over the past few decades, there has been a noticeable focus on adolescents' learning and participation activities. Surveys and studies conducted in academic schools in China have reported an increase in cases of adolescents experiencing learning difficulties. The previouis research has linked the concept of learning difficulties and disabilities within the broader cultural, social, and academic context. Existing studies shed light on various factors responsible for triggering learning difficulties and how to resolve them. The literature commonly identifies academic factors, such as the school environment and teaching styles, as potential causes of learning difficulties. However, studies have often neglected social elements, including the role of parents and an individual's self-efficacy. This study examines personal and social factors to analyze their impact on the psychological resilience of adolescents. A quantitative design was adopted where data was collected from adolescents across China through Wen Juan Xing. The findings imply that parental involvement, but not self-efficacy, significantly impacts psychological resilience. Additionally, it was discovered that parental involvement, self-efficacy, and psychological resilience weren’t mediated by achievement motivation. The findings from the study can be used by parents, managers, and other children welfare organizations to develop policies and processes that are supportive of the development and resilience of the adolescents.
Keywords: Resilience; self-efficacy; parental support; parental involvement; self-determination